A comparison study on the impact failure behavior of laminate and woven composites with consideration of strain rate effect and impact attitude. (July 2021) - Du, Chunlin; Wang, Huanfang; Zhao, Zhenqiang; Han, Lu; Zhang, Chao
Abstract: The anisotropy and heterogeneity of carbon fiber–reinforced polymer (CFRP) composites contribute to their complex failure characteristics, posing challenges for predicting their impact failure behavior. In this study, high-fidelity finite element models are established to predict the performance of laminated and woven composite panels impacted by a metallic projectile, with consideration of strain-rate effect and impact attitudes. The numerical models are experimentally validated and are applied to investigate the impact resistance of both composites under various impact conditions. The results indicate that the maximum ratio of delamination of laminated panel is about 0.4, which is greater than 0.2 of the woven panel. Woven panels can better withstand impact damage, while laminates are more prone to delamination under high-speed impacts loads. Highlights: A mathematical model is developed to calculate projectile attitude for impact test. The penetrating thresholds of CFRP panels are predicted using an efficient FE model. Differences on impact failure behavior of laminate and woven panels are clarified. Effects of projectile attitude on impact resistance of CFRP panels are illustrated.